'I feel like I have a disadvantage': how socio-economically disadvantaged students make the decision to study at a prestigious university. Issue 9 (2nd September 2019) - O'Sullivan, K.; Robson, J.; Winters, N.
ABSTRACT: This paper presents findings from an interpretative phenomenological analysis with 20 students from socio-economically disadvantaged backgrounds who were accepted onto a Foundation Year in Oxford University. It explores the factors that impacted on their decision to apply to a prestigious university and student's views on their transition to the prestigious university. The analysis highlighted four key factors: (1) The complex relationship students had with their schools and the wider education system; (2) The strong sense of agency they showed in overcoming a range of systemic and structural barriers; (3) Social relationships with family members, peers and the wider community; (4) The importance of the Foundation Year model in supporting transitions to the university. The identified factors have two key implications: (1) a need to engage in system-wide structural reform that empowers students to develop an agentic approach to HE choices and (2) a need for prestigious institutions to ensure that schools and teachers are empowered with cultural capital and knowledge of the admissions processes to support students' applications in an equitable way.